Opportunities to participate in formal and informal vocational learning activities and work-related outcomes in small professional services businesses - Coetzer, Alan [Verfasser]; Susomrith, Pattanee [Verfasser]; Ampofo, Emmanuel Twumasi [Verfasser] (My University, 2020)
"Small businesses are characterised by resources constraints; therefore, their managers need to know the exact nature of additional benefits, beyond knowledge and skill acquisition, that might accrue from employee participation in different types of learning activities. However, research that simultaneously examines the attitudinal and behavioural outcomes of opportunities to participate in formal and informal learning activities is sparse, especially in small businesses. The present study addresses this area of neglect by exploring associative relationships between opportunities for employees to participate in (1) formal learning activities and (2) informal learning activities and three important work-related outcomes: affective commitment, innovative behaviours, and work engagement. Data from 203 respondents in small professional services businesses were analysed and the results provide preliminary evidence that opportunities to participate in each type of learning activity are associated with differing outcomes. Opportunities to participate in formal learning activities were positively associated with heightened levels of affective commitment, work engagement, and innovative behaviours, while opportunities to participate in informal learning activities were positively related to work engagement. We provide suggestions for future research and outline practical implications of our analysis." (authors' abstract; BIBB-Doku)